Automated Laboratory Stand for Determining the Cogging Torque of a Small Permanent Magnet Electric Machine Using the MATLAB Environment - Paweł Strączyński; Sebastian Różowicz; Krzysztof Baran (Energies)
The phenomenon of the occurrence of cogging torque is one of the basic disadvantages of permanent magnet motors. An important aspect of designing a machine with magnetoelectric excitation is the formation of the magnetic circuit in such a way as to reduce this negative phenomenon. Due to the tolerances of the production of motor components, an important part of the design work is research into the properties of the designed machines on the built prototypes. This paper presents concepts and implementations for the construction of an automated laboratory station to determine the course of cogging torque. The measurement method, the concept, and implementations of the construction of the laboratory station are presented in this paper. The paper is summarized by a discussion of the results of laboratory tests on selected permanent magnet motors.